Rapid de novo evolution of lysis genes in single-stranded RNA phages - Karthik R. Chamakura (Nature Portfolio, 2020)
Leviviruses are phages with ssRNA genomes that encode a protein (Sgl) that induces host autolysis by interfering with bacterial cell wall synthesis. Identification of sgl genes is complicated by their small size and lack of sequence similarity. Here, Chamakura et al. use bioinformatic and experimental approaches to identify sgl genes in 244 leviviral genomes.